#TITLE_ALTERNATIVE# - TASLIM (NIM : 13206021); Pembimbing: Prof. Dr. Ir. Bambang Riyanto Trilaksono; Dr. Ir. Pek, STEVEN
The project title is hybrid power system which used Fuel Cell ,the one that uses hydrogen as the fuel, battery Li-Ion, and also supercapacitor. Overall systems are used to supply a load that has dynamic characteristic through a DC link (DC Bus). The main purpose of hybrid power system is to maintain excellent transient characteristic and also overall system performance. The main topic in this final project was DC-DC Converter that can operate in 2 quadrant of operation which means this converter can transfer power and energy from input to output or output to input. This converter was used in 2 auxiliary power source, battery and supercapacitor. This converter can maintain the balance of output power to DC Bus. The operation mode is divided to 2 types, discharging energy or charging energy. The result of designing DC Converter were the using of MOSFET as switch, Inductor 333 𝜇𝐻, Capacitor 140.625 𝜇𝐹, and supercapacitor circuit which contain 9 of 120F supercapacitor. The simulation result and implementation showed that the specifications were fulfilled. For controlling purpose, the current and voltage sensor were also included in implementation. Switching frequency that used was 25 kHz. This DC Converter control algorithm implemented with Proportional Integral and also Hysteresis. The Anti Windup application for PI controller was also used to achieve a reasonable control signal that produced. After designing and implementation of DC Converter, dynamic model from this DC Converter was also required. The model is used to obtain the dynamic characteristics. The model took state space model with took the Bus voltage as output, inductor current, bus voltage as states, and also 3 input variables: supercapacitor current, supercapacitor voltage, and duty cycle.